2020
DOI: 10.3390/fluids5040211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydraulic Mixing Efficiency in Widespread Models of Micromixers

Abstract: In this paper, we present the results of a systematic numerical study of the flow and mixing modes of fluids in micromixers of various configurations, in particular, an analysis of passive micromixers, the most widely used in practice, as well as the main methods to intensify mixing. The advantages of microstructure reactors can significantly reduce reaction times and increase productivity compared to traditional bulk reactors. Four different geometries of micromixers, including the straight T-shaped microchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Gidde et al (2017) demonstrated that the circular chambers lead to a higher pressure drop than the square chambers, but high mixing efficiency. Minakov et al (2020) compared four different types of micromixers and found that a vortex mixing in cylindrical chambers has 600 times more mixing efficiency than a straight T-mixer. It means that the cylindrical chamber of micromixer has significant advantage for mixing enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Gidde et al (2017) demonstrated that the circular chambers lead to a higher pressure drop than the square chambers, but high mixing efficiency. Minakov et al (2020) compared four different types of micromixers and found that a vortex mixing in cylindrical chambers has 600 times more mixing efficiency than a straight T-mixer. It means that the cylindrical chamber of micromixer has significant advantage for mixing enhancement.…”
Section: Introductionmentioning
confidence: 99%